PERANCANGAN APLIKASI SISTEM MONITORING STUNTING DI PUSKESMAS PAMULANG MENGGUNAKAN METODE FUZZY TSUKAMOTO BERBASIS WEB - Wawan Setiawan; Intan Kumalasari (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
Stunting is a chronic nutritional problem that remains a significant public health challenge, including in the working area of Puskesmas Pamulang, where the recording and analysis of anthropometric data for toddlers are still carried out manually, making them prone to errors and delays in reporting. This study aims to design and implement a web-based stunting monitoring system to improve the effectiveness of recording, processing, and presenting nutritional status monitoring results. The Fuzzy Tsukamoto method is applied to automatically assess nutritional status based on age, weight, and height variables. The study utilized a data sample of 20 toddlers from Posyandu Anggrek 2 as the basis for fuzzy logic testing. System development included the stages of requirements analysis, database and UML design, implementation using PHP–MySQL, and testing using Black Box Testing. The system displays real-time predictions of toddlers’ nutritional status (overnutrition, normal nutrition, undernutrition) through fuzzification, rule-based inference, and defuzzification processes. The testing results show that all system functions operate as intended, and the classification of nutritional status using the Fuzzy Tsukamoto method produces outputs consistent with manual calculations. The implementation of this system enhances accuracy and speed in monitoring, simplifies reporting for posyandu cadres, and supports nutrition officers in decision-making. Therefore, the application has the potential to serve as a supporting tool in accelerating stunting prevention efforts at Puskesmas Pamulang.